THE CURRENT STATE OF PHYSICS EDUCATION AND PEDAGOGICAL CHALLENGES IN GENERAL SECONDARY SCHOOLS (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This article provides a comprehensive analysis of the current state of physics education in general secondary schools, emphasizing the pedagogical challenges faced by teachers and schoolchildrens. Physics, as a core science subject, plays a vital role in developing scientific literacy and analytical skills. However, numerous factors hinder its effective teaching and learning, including limited laboratory resources, outdated methodologies, insufficient teacher training, and schoolchildrens’ declining interest in science subjects. The article discusses these issues in depth and proposes practical solutions such as improved teacher professional development, curriculum reform, integration of modern technologies, and the promotion of student-centered learning environments.